People are essential to linking biodiversity data. (27th November 2020) - Groom, Quentin; Güntsch, Anton; Huybrechts, Pieter; Kearney, Nicole; Leachman, Siobhan; Nicolson, Nicky; Page, Roderic D M; Shorthouse, David P; Thessen, Anne E; Haston, Elspeth
Abstract: People are one of the best known and most stable entities in the biodiversity knowledge graph. The wealth of public information associated with people and the ability to identify them uniquely open up the possibility to make more use of these data in biodiversity science. Person data are almost always associated with entities such as specimens, molecular sequences, taxonomic names, observations, images, traits and publications. For example, the digitization and the aggregation of specimen data from museums and herbaria allow us to view a scientist's specimen collecting in conjunction with the whole corpus of their works. However, the metadata of these entities are also useful in validating data, integrating data across collections and institutional databases and can be the basis of future research into biodiversity and science. In addition, the ability to reliably credit collectors for their work has the potential to change the incentive structure to promote improved curation and maintenance of natural history collections.